2005
DOI: 10.1093/aob/mci149
|View full text |Cite
|
Sign up to set email alerts
|

Differences in in vitro Pollen Germination and Pollen Tube Growth of Cotton Cultivars in Response to High Temperature

Abstract: Based on principal component analysis, it is concluded that higher pollen germination percentages and longer pollen tubes under optimum conditions and with optimum temperatures above 32 degrees C for pollen germination would indicate tolerance to high temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
233
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(270 citation statements)
references
References 41 publications
31
233
1
5
Order By: Relevance
“…The differences found between in vitro pollen viability studies in relation to the yellow passion fruit are probably due to the genetic origin of the material itself, environmental conditions and the culture mediums used for germination. Kakani et al (2005) confirms that the differences observed during in vitro pollen germination and the growth of the pollen tube in relation to twelve cotton cultivars (Gossypium hirsutum) were, in fact, related to variations in the cultivars themselves. Similarly, Franzon et al (2005) working with feijoa (Acca sellowiana (Berg) Burret) reported differences between species and between cultivars within the same species, in relation to the necessary culture medium conditions for in vitro pollen germination.…”
Section: Discussionsupporting
confidence: 74%
“…The differences found between in vitro pollen viability studies in relation to the yellow passion fruit are probably due to the genetic origin of the material itself, environmental conditions and the culture mediums used for germination. Kakani et al (2005) confirms that the differences observed during in vitro pollen germination and the growth of the pollen tube in relation to twelve cotton cultivars (Gossypium hirsutum) were, in fact, related to variations in the cultivars themselves. Similarly, Franzon et al (2005) working with feijoa (Acca sellowiana (Berg) Burret) reported differences between species and between cultivars within the same species, in relation to the necessary culture medium conditions for in vitro pollen germination.…”
Section: Discussionsupporting
confidence: 74%
“…For example, while for many species native to or cultivated in temperate regions optimum temperatures in the range 15ºC-25ºC are usually recorded [examples include Arabidopsis thaliana (22ºC, Boavida and McCormick, 2007), sweet cherry (25ºC, Lewis, 1942), or almond (Prunus dulcis Mill.) and peach (16ºC and 23ºC respectively, Weinbaum et al, 1984)], optimum temperatures above 25ºC have been reported for several subtropical and tropical species such as Datura stramonium (33ºC, Buchholz and Blakeslee, 1927), Oenothera (33ºC, Lewis, 1942), groundnut (30ºC for pollen germination and 34ºC for pollen tube growth, Kakani et al, 2002) or cotton (Gossypium hirsutum L.) (from 28ºC to 32ºC, Kakani et al, 2005). These adaptations can be best seen in natural populations that flower during extremely high or low temperatures.…”
Section: Genetic Variation In the Reproductive Processes Under Tempermentioning
confidence: 99%
“…Genotype-specific responses have been reported for stress applied during microsporogenesis affecting carbohydrate metabolism, degeneration of the tapetal tissues, pollen wall architecture, pollen morphology, pollen viability, anther dehiscence and pollen production (Aloni et al, 2001;Koti et al, 2005;Oliver et al, 2005;Porch and Jahn, 2001;Prasad et al, 2006;Pressman et al, 2002;Srinivasan et al, 1999;Suzuki et al, 2001). At the post-anthesis level, pollen germination (Hedhly et al, 2005a;Kakani et al, 2002Kakani et al, , 2005, pollen tube growth rate (Clarke and Siddique, 2004;Hedhly et al, 2004;Srinivasan et al, 1999), and pollen dynamics (Hedhly et al, 2005a) also show genotype-specific responses.…”
Section: Genetic Variation In the Reproductive Processes Under Tempermentioning
confidence: 99%
“…Temperature is considered one of the environmental factors that most influences the reproductive process of plants (Kakani et al, 2005). To test the response of in vitro pollen grain germination and pollen tube growth, studies examining variations in temperature and the use of linear and non-linear regression models have been widely used.…”
Section: Resultsmentioning
confidence: 99%
“…This subject has been studied in several different crops such as pistachios (Acar and Kakami, 2010), peaches (Hedhly et al, 2005), peanuts (Kakani et al, 2002), cotton (Kakani et al, 2005), sorghum (Prasad et al, 2011), Capsicum (Reddy and Kakani, 2007) and papaya (Tamaki et al, 2011). Based on their findings, these authors have defined the cardinal temperatures: the minimum temperature (T min ) at which pollen grains germinate, the optimal temperature at which the pollen grain germination reaches the maximum (T opt ) and the maximum temperature (T max ) after which pollen grain germination does not occur.…”
Section: Introductionmentioning
confidence: 99%